Development of Interactive Edugame Learning Media Based on Snakes & Ladders to Improve IPAS Learning Outcomes - Fatmawati, Erma; Andriani, Aldina Eka (Jurnal Pijar Mipa, 2024)
The use of learning media that is a game has never been developed by teachers, resulting in low learning outcomes of IPAS light and sound material. The purpose of this study was to develop, test the feasibility, and effectiveness of interactive edugame learning media based on snakes & ladders to improve the cognitive learning outcomes of IPAS for fifth grade students of SD Negeri Candi 01 Semarang City. The type of research used is Research and Development (R&D) research with the Borg and Gall development model. The subjects of this research were 24 fifth grade students of SD Negeri Candi 01 Semarang City. Data collection techniques used non-test techniques (observation, interviews, questionnaires, data and documentation) and test techniques (pretest and posttest). The data analysis technique begins with the normality test, then the T test and the N-Gain test to show the final results. The results of this study are as follows 1) Snakes & ladders-based interactive edugame learning media was developed using Canva and Genially applications in the form of a flipbook with components, namely cover, preface, table of contents, character introduction, concept map, learning outcomes, learning objectives, materials, games, LKPD, images, animations, experimental videos, and HOTS questions. 2) The results of the feasibility test from media experts obtained a score of 91% with a very feasible category and material experts obtained a score of 93% with a very feasible category. 3) The effectiveness of snakes & ladders-based interactive edugame learning media comes from the results of the pretest and posttest, based on the cognitive learning outcomes of students showing an increase in change, namely the normality test analysis shows that the data is normally distributed. The T test results obtained Sig. (2-tailled) 0.001 <0.05. The N-Gain test results were 0.84 with high criteria. The conclusion of the development of interactive edugame media based on snakes & ladders was successfully developed with very feasible and effective to improve the cognitive learning outcomes of IPAS fifth grade students of SD Negeri Candi 01 Semarang City.